KEY CHARACTERISTICS OF SIBLING RELATIONSHIPS AND THEIR IMPACT ON INDIVIDUAL DEVELOPMENT - Peleg, Lilach (E-Journal VFU, 2025)
The term "siblings" resonates universally, representing a fundamental relationship in families with multiple children. Parents often aspire for strong sibling bonds that foster unity and continuity across generations. Research highlights the profound influence of positive sibling relationships on an individual’s development and well-being throughout life. Sibling relationships are typically the longest-lasting connections individuals maintain. This article explores the key psychological characteristics and theoretical frameworks that shape sibling dynamics and their impact on the individual. It emphasizes the roles of warmth, closeness, rivalry, and conflict in sibling relationships, alongside the influence of parental factors.